Migration of dissolved organic carbon in biochars and biochar‑mineral complexes - Lin, Yun; Munroe, Paul; Joseph, Stephen; Henderson, Rita (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to determine the contribution of dissolved organic carbon (DOC) from a biochar mineral complex (BMC), so as to better understand the interactions between DOC, biochar, clay, and minerals during thermal treatment, and the effects of BMC on amended soils. The BMC was prepared by heating a mixture of a H3PO4‑treated saligna biochar from Acacia saligna, clays, other minerals, and chicken manure. The BMC was applied to a sandy loam soil in Western Australia, where wheat was grown. Liquid chromatography‑organic carbon detection (LC‑OCD) tests were carried out on water extracts from the untreated biochar, the BMC, the BMC‑amended soil, and on a control soil to measure the DOC concentration. LC‑OCD tests provide a fingerprint of the DOC, which allows the fractions of DOC to be determined. Thermal processing enhanced the reaction of the A. saligna biochar with manure, clays and minerals, and affected the distribution of the DOC fractions. Notably, the process leads to immobilization of hydrophobic DOC and to an increase in the concentration of low‑molecular‑weight neutrals in the BMC. The application of the BMC to soil increases the DOC in the amended soil, especially the biopolymer fraction.